2007
DOI: 10.1002/cjoc.200790229
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interaction of Colloidal Gold with Taq DNA Polymerase

Abstract: The interaction of colloidal gold with Taq DNA polymerase (Taq) was investigated in this study. Taq-gold conjugate was formed by adding the enzyme to the colloidal gold solution, as evidenced by UV-Vis spectroscopy, X-ray photoelectron spectroscopy, and photon cross correlation spectroscopy measurements. The conjugate was further characterized by transmission electron microscopy. It was found that the Taq-gold conjugate particles were still spherical and well-dispersed. The influence of gold nanoparticles on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Other reports also confirmed the presence of interactions between nanoparticles and DNA polymerases. 30,[58][59][60] Lin's group proposed an alternative mechanism that was associated the physical property of AuNPs. They proposed that heat conductivity of AuNPs played an important role in increasing the thermal cycling efficiency of the PCR reaction, hence the required reaction time could be dramatically shortened.…”
Section: Proposed Mechanisms For Nanopcrmentioning
confidence: 99%
“…Other reports also confirmed the presence of interactions between nanoparticles and DNA polymerases. 30,[58][59][60] Lin's group proposed an alternative mechanism that was associated the physical property of AuNPs. They proposed that heat conductivity of AuNPs played an important role in increasing the thermal cycling efficiency of the PCR reaction, hence the required reaction time could be dramatically shortened.…”
Section: Proposed Mechanisms For Nanopcrmentioning
confidence: 99%
“…Several mechanisms have been proposed to account for the observed effects. We initially proposed that AuNPs realized their functions via selective binding to single‐stranded DNA, resembling single‐stranded binding (SSB) protein,23 while subsequent studies suggested that the interactions between AuNPs and polymerases played an important role as well 25–27. We thus propose that AuNPs possess multiple functions in complicated and diverse PCR systems, but one of these functions may predominate in a specific system.…”
Section: Introductionmentioning
confidence: 99%